Do present damage and health perception in patients with systemic lupus erythematosus predict extent of future damage?: a prospective study. Issue 10 (1st October 2000) - Stoll, Thomas; Sutcliffe, Nurhan; Klaghofer, Richard; Isenberg, David A
Abstract : OBJECTIVE: To study whether either initial damage, disease activity, disease duration, age, a drug score, or health status would predict an increase in damage in patients with systemic lupus erythematosus (SLE) within the next three years. METHODS: A three year prospective longitudinal study of a cohort of 141 consecutive patients with SLE attending a specialist lupus outpatient clinic from their first assessment between July 1994 and February 1995. Disease activity was assessed using the BILAG system, health status by the Medical Outcome Survey Short Form 20 with an extra question about fatigue (SF-20+), and damage by the SLICC/ACR Damage Index (SDI). Damage was reassessed three years later. Statistical analysis was carried out using logistic regression analysis (logXact). RESULTS: 133 female and 8 male patients with SLE (97 white subjects, 16 Afro-Caribbeans, 22 Asians, and 6 others) were included. Their mean (SD) age at inclusion was 41.1 (12.5) years and their disease duration 10.2 (6.3) years. The mean measures at inclusion were: total BILAG 5.2 (range 0–17), total SDI 1.2 (0–7), drug score 1.2 (0–3); SF-20+: physical 58 (0–100), role 54 (0–100), social functioning 71 (0–100), mental health 64 (16–100), health perception 44 (0–100), pain 53 (0–100), fatigue 59 (0–100). Four patients were lost to follow up because they had moved. At three years in 33 patients the total SDI had increased to a mean of 1.5 (0–7) (n=130). Moreover, seven patients had the maximum damage as they had died during the follow up period. The only variables with an independent and significant contribution in predicting damage at three years were the total damage score (odds ratio (OR)=1.46; 95% CI 1.04 to 2.05), and health perception (OR=0.96; 95% CI 0.93 to 0.99) at inclusion. CONCLUSIONS: Of all the variables at inclusion only the total damage score and SF-20+: health perception, significantly predicted an increase in damage, for patients with SLE, three years later.